The Legal Politics of the Government to Provide Legal Certainty Related to the Practice of Pawning on A Paid Rent Based on Justice Value - Arpangi Arpangi (JURNAL AKTA, 2022)
Pawning has become a trend in society because the procedures and requirements are easy, simple, and uncomplicated so that people immediately get money. So it is not uncommon for people to guarantee their goods in pawning activities. Based on the formulation of Article 1150 of the Civil Code, it can be seen that pawning is a material security right on certain movable objects belonging to the debtor or another person on behalf of the debtor to serve as collateral for the settlement of certain debts, which gives priority rights (preference) to the holder of the lien over other creditors. , after prioritizing the costs for the auction and the cost of rescuing the pawned goods taken from the sale proceeds through a public auction of the pawned goods. As material rights, liens continue to follow the object or goods pledged in the hands of whoever holds it (droit de suite). Likewise, it contains a right to sue because the recipient of the pledge has the right to claim the lost goods back. This provision is as contained in Article 1152 Paragraph (3) of the Civil Code. Article 1152 paragraph (4) of the Civil Code stipulates that if later it turns out that the pawnbroker does not actually have the right to alienate the goods, for example, he is only the tenant or the borrower of the goods, then the lien rights of the pledge holder cannot be cancelled.